Bibliometric analysis of the scientific production on inguinal hernia surgery in the web of science - Carhuallanqui-Ciocca, Eros Ignacio; Echevarría-Quispe, Johssy Yelma; Hernández-Vásquez, Akram; Díaz-Ruiz, Renato; Azañedo, Diego (Frontiers in Surgery, 2023)
Objectives. To describe the bibliometric characteristics of the world scientific production in inguinal hernia surgery using the Web of Science Core Collection (WoS) database. Materials and methods. A search for original articles published in the WoS up to December 2021 was carried out. Bibliometric analysis was performed using the Bibliometrix data package in R and VOSviewer, version 1.6.17. Results. A total of 3,814 articles were identified in the database, with an annual average of 81 published articles and sustained growth with the highest number of publications in 2021. The article "International Guidelines for Groin Hernia Management” published in 2016 was the most cited (633 citations). The United States was the country of the corresponding author with the highest number of published articles (728 articles). The author with the highest number of citations was Rosenberg J., affiliated with the University of Copenhagen, with 15,859 citations. The journal “Hernia” had the highest number of articles published on inguinal hernias in the WoS, representing 18% of the total number of articles. Finally, the keywords most used were “herniorrhaphy” and “hernioplasty” in 2008, and more recently: “single incision” “society guidelines'' and “single port”. Conclusions. The scientific production of original articles on inguinal hernia surgery has increased. There is currently great interest in research on minimally invasive surgical methods and standardization of procedures based on clinical practice guidelines.